Early Warning: Using Competitive Intelligence to Anticipate Market Shifts, Control Risk, and Create Powerful Strategies - Gilad, Benjamin (Journal of Sustainable Competitive Intelligence, 2012)
Surprise is rarely a good thing in business. Unexpected developments range in their effects from inconvenient to disastrous. To avoid being blindsided, companies must develop a Competitive Early Warning system, or CEW, which combines strategic planning, competitive intelligence, and management action. Such systems let organizations manage risk more effectively and prevent "industry dissonance" - when market realities outpace corporate strategies. "Early Warning" reveals how to: change strategy to meet new realities; learn from the mistakes of others via the book's eye-opening stories; avoid common tactics like benchmarking and using consultants, which may do more harm than good; and tell executives what they need to know - not what they want to hear. Each chapter ends with a Manager's Checklist of key points, and the book includes numerous charts, tables, and tools. With strong opinions and wry humor, world-recognized expert Gilad reveals how to anticipate and react to early signs of trouble. Book Description Publication Date: September 12, 2003 Clique Aqui